Sosialisasi Pengenalan Website Sistem Informasi Posyandu pada Kader Posyandu di Kelurahan Cipawitra: Website-Based Posyandu Information System: Introduction and Socialization to Cadres in Cipawitra Subdistrict - Purnia, Dini Silvi; Supriadi, Deddy; Simpony, Bambang Kelana; Cahyadi, Cepi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This community service program aims to enhance the digital literacy of Posyandu cadres in Cipawitra Subdistrict, Tasikmalaya, through the socialization and training of a Posyandu information system website. The main issue addressed is the manual and uneven dissemination of Posyandu activity information, which leads to low public participation. The program began with a needs assessment, followed by the design and development of the website, socialization, training, and implementation evaluation. The website provides key information such as schedules, services, and Posyandu locations. The results showed improved understanding and skills among cadres in accessing and managing digital information. This program encourages the adoption of technology at the community level and strengthens the independent management of health services. Outcomes, including increased cadre capacity, a published scientific article, and comprehensive documentation of the activities, support program sustainability.